2010
DOI: 10.1352/1944-7558-115.6.473
|View full text |Cite
|
Sign up to set email alerts
|

Self-Injurious Behavior and Fragile X Syndrome: Findings From the National Fragile X Survey

Abstract: We used National Fragile X Survey data in order to examine reported self-injurious behavior (SIB) to (a) generate lifetime and point prevalence estimates, (b) document detailed features of SIB (frequency, types, location, severity) in relation to gender, and (c) compare comorbid conditions between matched pairs (SIB vs. no SIB). Results indicate significant gender differences in frequency, topography, and location of SIB as well as sleep difficulties, comorbid conditions, pain sensitivity, and seizures. Matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 13 publications
5
70
1
1
Order By: Relevance
“…However, it is of note that the rates of SIB and aggression reported in this study are far higher than rates cited in previous research (e.g. Bailey et al, 2008;Symons et al, 2010). These differing results may be explained by the age range of the individuals assessed by each respective study.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…However, it is of note that the rates of SIB and aggression reported in this study are far higher than rates cited in previous research (e.g. Bailey et al, 2008;Symons et al, 2010). These differing results may be explained by the age range of the individuals assessed by each respective study.…”
Section: Discussioncontrasting
confidence: 82%
“…Bailey, Raspa, Olmsted, and Holiday (2008) estimate that 38% of males and 14% of females with the FMR1 full mutation engaged in aggressive behavior. A nationwide study conducted by Symons et al (2010) found that 41% of males and 16% of females with the FMR1 full mutation engaged in SIB. This study also found that the onset of SIB occurred around the age of three years, with no gender differences found regarding the age of onset reported.…”
mentioning
confidence: 99%
“…The severity of the manifestation of the syndrome is variable, but individuals with FXS typically show marked behavioural features including deficits in attention, language and IQ; hyperactivity; anxiety; self-injury (particularly hand-biting); aggression; hyperarousal; stereotypies; and social difficulties, including gaze avoidance (Symons, Byiers, Raspa, Bishop & Bailey, 2010;Lachiewicz, et al, 1994;Bailey, Raspa, Olmsted & Holiday, 2008). The presentation of the FXS is quantitatively gender The hypothalamic-pituitary adrenal (HPA) axis is one of the body s main stress effector systems and is a circuit of interest in Fragile X research.…”
Section: Resultsmentioning
confidence: 99%
“…These problem behaviors are especially detrimental to family functioning as they can significantly impede an individual's ability to participate in daily activities. Self-injurious behavior typically appears fairly early in development; onset for most individuals (both male and female) occurs at 1-3 years of age [24]. Aggression typically occurs later, mostly during the pubescent and postpubescent period [25].…”
Section: Cognitive Behavioral and Language Features Of Fxsmentioning
confidence: 99%